A Empirical Research on Finding Impact of Narcissist Personality Factors (NPF) In Cosmetic Advertising among Youth in Bangalore City - Sayed Kazim, V.P.Sriram, A.Arun (International Journal of Advanced Science and Technology, 2020)
In this research paper, the researcher majorly focuses on the causes and its effects of cosmetic advertisement and their personality related disorders on consumers. Also, the researcher further focuses on behavioral intention of the consumers and their respective impact towards the purchase of cosmetics. The research study was carried out in Bengaluru city, where the samples been collected among the youth of south India. Here, the researcher basically wants to highlight the various personality disorders and their behavioral intention to purchase cosmetics. Further, the researcher had collected required number of sample through an appropriate research methodology of descriptive in nature. The Outcome of the research study would further reveals impact of various personality disorder’s on consumer intention towards the purchase of various branded cosmetic products. Further, the researcher ultimately want to measure the greater impact of demographic on various research variables which are deployed in the study. Keywords: Narcissist, Personality, Cosmetic-Advertising, Youth